The screening process of a patient with low back pain and suspected thoracic myelopathy: a case report - Christe, G.; Hall, Toby (Maney Publishing, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis GroupBackground: Thoracic disc herniations are rare and difficult to diagnose. Myelopathy is a potential consequence that can lead to irreversible neurological impairment if not treated appropriately. It is incumbent on all clinicians who see patients with low back pain (LBP) to be aware of such pathologies. This case describes a screening process in the detection of a rare serious spinal pathology and discusses the use of red flags and central nervous system signs and symptoms in the decision leading to immediate referral. Case Description: The subject in this case was a 69-year-old male referred to physical therapy for the treatment of LBP after having seen two medical doctors. He presented with severe spinal pain with gait disturbance, postural balance deficits and bilateral loss of plantar flexor strength. Decreased sensation in the buttocks and a subtle episode of urinary incontinence were also present. Outcomes: Based on the results of the history and physical examination, the patient was referred back to his medical practitioner, who ordered magnetic resonance imaging. A thoracic disc herniation associated with spondyloarthritis at T10–11 causing myelopathy was detected, and the patient underwent immediate decompressive surgery. One month following initial evaluation, the patient had completely recovered without any neurological compromise. Discussion: This case highlights the importance of the screening of serious pathologies and the assessment of central nervous impairments in certain cases of LBP. The integration of a cluster of subjective and physical examination findings led to the prompt referral of this patient for urgent medical attention. Level of Evidence: 4.